Oral Tradition in The Closing Of Prayer Delivery at The Al-Yahdi Klambir V Foundation in The Medan Helvetia Subdistrict (Anthropological Linguistics Study) - Tria Wardani; Nurul Ramadhan; Mutiara Ramadhan; Nursukma Suri (Jurnal Salaka : Jurnal Bahasa, Sastra, dan Budaya Indonesia, 2025)
This study aims to describe the form of oral tradition in the closing of prayer activities at the Al-Yahdi Klambir V Foundation in Medan through an anthropological-linguistic perspective. The focus of the study is on the use of Shalawat Pembuka Pintu Rezeki (Prayer for Opening the Door to Sustenance) as the closing of the yasinan ritual, which is a unique linguistic and cultural phenomenon. The research uses a qualitative approach with an anthropological ethnographic design through participatory observation, in-depth interviews, and documentation. The analysis was conducted by looking at the relationship between language form, cultural context, social function, and symbolic meaning in the practice of oral tradition. The results of the study show that the recitation of Shalawat not only functions as a religious expression but also as a medium for conveying cultural values that strengthen group identity, solidarity, and continuity of tradition. Linguistically, the repetition, intonation, language formulas, and performativity in Shalawat are markers of local wisdom and living cultural expressions. This study confirms that oral traditions in religious rituals are a form of cultural practice that is passed down through language and performance. Keywords: Oral Tradition, Prayer Delivery, Anthropolinguistics